2018
DOI: 10.1117/1.jbo.23.3.036013
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative real-time optical imaging of the tissue metabolic rate of oxygen consumption

Abstract: Abstract. The tissue metabolic rate of oxygen consumption (tMRO 2 ) is a clinically relevant marker for a number of pathologies including cancer and arterial occlusive disease. We present and validate a noncontact method for quantitatively mapping tMRO 2 over a wide, scalable field of view at 16 frames∕s. We achieve this by developing a dual-wavelength, near-infrared coherent spatial frequency-domain imaging (cSFDI) system to calculate tissue optical properties (i.e., absorption, μ a , and reduced scattering, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 50 publications
5
42
1
Order By: Relevance
“…In this work, CMRO 2 was computed differently for the two cases of normoglycemia and hyperglycemia using the following formulas as described in detail in Ref. , CMRO2{α×CBF×Hb:0.5emnormal4×d()Hbr/italicdt:0.5emhyper …”
Section: Methodsmentioning
confidence: 99%
“…In this work, CMRO 2 was computed differently for the two cases of normoglycemia and hyperglycemia using the following formulas as described in detail in Ref. , CMRO2{α×CBF×Hb:0.5emnormal4×d()Hbr/italicdt:0.5emhyper …”
Section: Methodsmentioning
confidence: 99%
“…76 , [80][81][82] The concept has been extended to real-time measurements using SSOP combined with speckle flow measurement into coherent-SSOP (c-SSOP), which has been validated onto arm-cuff occlusions in human subject and is now tested clinically. 83,84…”
Section: Sfdi and Specklementioning
confidence: 99%
“…This quantity is equivalent to the concentration of deoxygenated hemoglobin that arrived in a venule following oxygen extraction by the brain. Therefore, within our measurement paradigm [6], Eq. (4) is re-written as:…”
Section: Absolute Cerebral Metabolic Rate Of Oxygen (Cmro 2 ) Calculamentioning
confidence: 99%
“…Diffuse optical imaging (DOI) techniques are an inroad to addressing this problem, as they are noncontact and use non-harmful visible and near-infrared light to probe tissue absorption and scattering for endogenous contrast. Recently, we demonstrated that the combination of Spatial Frequency Domain Imaging (SFDI) and Laser Speckle Imaging (LSI)) can quantify tissue metabolic changes with high spatial and temporal resolution [6]. We also recently applied high-speed LSI [7] and SFDI [8] to measure perfusion, oxygenation, and tissue scattering in the brain in a cardiac arrest (CA) model of global cerebral ischemia.…”
Section: Introductionmentioning
confidence: 99%